Lead free efficient perovskite solar cell device Optimization and defect study using Mg doped CuCrO2 as HTL and WO3 as ETL. (1st September 2022) - Sarkar, D.K; Mahmud Hasan, A.K.; Mottakin, M.; Selvanathan, Vidhya; Sobayel, K.; Ariful Islam, Md.; Muhammad, Ghulam; Aminuzzaman, Mohammod; Shahiduzzaman, Md.; Sopian, Kamaruzzaman; Akhtaruzzaman, Md.
Abstract: An n -i-p architecture perovskite solar cell (PSC) has been suggested and modelled employing Pb free CH3 NH3 SnI3 absorber layer. A relative investigation for WO3 (ETL) and Mg-CuCrO2 (HTL) with different thickness, carrier concentration, interfacial layer (IL) defect tolerance factor, impact of temperature on device performance have been portrayed by SCAPS-1D simulator. A lower thickness of ETL and HTL is quite effective to produce better efficiency. The proposed FTO/WO3 /CH3 NH3 SnI3 /Mg-CuCrO2 /Au device shows the maximum Voc, Jsc, FF and PCE of 1.02 V, 37.95 mA/cm 2, 71.38 %, 27.53 %, respectively. The carrier concentrations NA and ND were optimized at 1x10 14 c m - 3 and 1x10 16 c m - 3 . After those ideals, the projected PSC device's photovoltaic presentation was considerably reduced. The interfacial layer 1 (IL1) and interfacial layer 2 (IL2) exhibited the defect tolerance level of 1x10 11 c m - 2 and 1x10 16 c m - 2, respectively. It was found that Au as a back-contact could produce the highest PCE among other back contact metals. The ambient temperature proved to be ideal one to generate the highest PCE since elevated temperatures lead to reduce Voc and PCE thereby. The suggested ETL and HTL have been proved to be alternative inorganic charge transporting materials which could regulate the device performance as well as stability into the environmental atmosphere.